The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1111/j.1537-2995.2008.01684.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a high‐throughput HLA antibody screening assay for use with platelet donors

Abstract: Background-Passive infusion of HLA antibodies has been implicated in transfusion reactions. A rapid, inexpensive method of screening blood donors for HLA antibodies might reduce the incidence of reactions. A high-throughput microbead-flow analyzer HLA antibody detection technique was compared with an ELISA method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 14 publications
4
33
1
1
Order By: Relevance
“…The Luminex assay was also used in two recent smaller studies of HLA alloimmunization in blood donors, both of which reported higher rates than what we observed at the 3SD cutoff but similar to our results at the NBG cutoff of 2.2 10,26. Powers et al tested 1027 women and 26 males with a history of transfusion.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The Luminex assay was also used in two recent smaller studies of HLA alloimmunization in blood donors, both of which reported higher rates than what we observed at the 3SD cutoff but similar to our results at the NBG cutoff of 2.2 10,26. Powers et al tested 1027 women and 26 males with a history of transfusion.…”
Section: Discussionsupporting
confidence: 89%
“…These ELISA results are almost identical to the results of a larger study of 1043 donors reporting HLA antibodies in 9.8% of females and none in males 27. The most likely explanation for the high prevalence using microbead flow assays observed in the two smaller studies10,26 is that they used the manufacturer's suggested NBG cutoff of 2.2. We found similar results in our larger study when we used the same cutoffs.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…[20][21][22][23] These systems are generally more sensitive than LCA, and several commercial kits are currently available. 20,[24][25][26] Antibodies against human platelet antigens (HPAs) can also be generated in response to platelet transfusion. These antigens appear to be less immunogenic than HLA antigens, resulting in a lower frequency of HPA alloimmunization, which ranges from 0% to 2%, depending on the patient population.…”
Section: Introductionmentioning
confidence: 99%